Amino-reinforced polylactic acid-based nanofiber membrane as well as preparation method and application thereof

By introducing high -active amino groups in polylactic acid, hydrogen bonds are formed to enhance its compounding and electrical activity, solving the problem of poor tensile strength and friction effect in the field of air filtration in the field of air filtration. The air filtration effect.

CN119345923AActive Publication Date: 2025-01-24SHENHUA SHENDONG COAL GRP +4
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411626907.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-01-24
Estimated Expiration
2044-11-14

AI Technical Summary

Technical Problem

The number of chain active groups of polylactic acid is small and has a low degree of polarization, which leads to poor tensile strength and triboelectric effect, affecting its application in the field of air filtration.

Method used

By introducing highly active amino groups and using the amino groups to form hydrogen bonds with polylactic acid chain groups to increase the hydrogen bond density, thereby strengthening the stereocomplexation and electroactivity of polylactic acid, an amino-reinforced polylactic acid-based nanofiber membrane was prepared.

Benefits of technology

The electrical activity, gas separation capacity, anti -microbial activity and filtration effect of amino -enhanced polymal nano -fiber membrane, and achieve efficient and low -resistance air filtration, and long -term storage will not affect the filter potential.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119345923A_ABST
    Figure CN119345923A_ABST
Patent Text Reader

Abstract

The invention discloses an amino-enhanced polylactic acid-based nanofiber membrane and a preparation method and application thereof, and belongs to the technical field of air filtering membrane materials. An aminated polylactic acid fiber membrane (MSC-PLA fiber membrane) is obtained by introducing high-activity amino to increase hydrogen bond density to promote stereocomplex formation; a triboelectric nano-generator basis is provided, charges can be stably collected and a potential field can be formed by compounding with an electrode membrane, and a triboelectric nano-generator structure is formed in a membrane combination mode, so that the amino-enhanced polylactic acid-based nanofiber membrane with high electroactivity, antimicrobial activity, excellent PMs filtering effect and low filtering resistance is obtained; and the potential of the filter material is not influenced by long-term storage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of air filtration membrane materials, and in particular to an amino-reinforced polylactic acid-based nanofiber membrane and a preparation method and application thereof. Background Art

[0002] With the rapid development of global industrialization, the problem of air pollution is becoming increasingly serious. In order to block the harm of air pollutants to human health, it is urgent to develop air filter membranes that can inactivate microorganisms for a long time, have low filtration resistance, and have excellent filtration effects. Existing air filter membranes are made of polypropylene fibers, which increase the filtration efficiency of particulate matter by mechanical filtration and the capture of particles by charged fibers. However, polypropylene is difficult to degrade naturally, so it is not conducive to the environmental protection concept of green and sustainable development.

[0003] Polylactic acid is a biodegradable material whose raw materials are made of starch extracted from plants. The carbon dioxide and water produced by degradation in nature can be reused by plants through photosynthesis, which embodies a green cycle of recyclability and sustainable development. Due to its excellent mechanical properties, good biocompatibility, non-toxicity and mildness, it has broad application prospects in the field of air filtration. At the same time, polylactic acid exhibits shear triboelectricity due to the chiral center in its molecular chain. It can generate voltage through mechanical action without the need for polarization treatment of an external electric field. This method is simple, efficient, and easy to achieve large-scale production. However, polylactic acid has the problems of a small number of chain active groups and a low degree of polarization, which affects the tensile strength and triboelectric effect of polylactic acid. Summary of the invention

[0004] The present invention provides an amino-reinforced polylactic acid-based nanofiber membrane and a preparation method and application thereof, which effectively solves the technical problem that the tensile strength and triboelectric effect of polylactic acid are poor due to the small number of active groups in the polylactic acid chain and the low degree of polarization. The present invention strengthens the stereocomplexation of polylactic acid through amino metal-organic framework materials, enhances the electrical activity and gas separation ability of the nanofiber membrane, and enables the fiber membrane to have the characteristics of harmful gas separation, high efficiency, low resistance and antibacterial.

[0005] The present invention provides a method for preparing an amino-reinforced polylactic acid-based nanofiber membrane, comprising the following steps:

[0006] The left-handed polylactic acid and the right-handed polylactic acid are used as raw materials, respectively dissolved in a solvent to obtain a first spinning solution and a second spinning solution, and then mixed to obtain a spinning solution.

[0007] The aminated metal organic framework powder is added to the spinning solution to obtain a blended solution, and the blended solution is electrostatically spun to form hydrogen bonds between the amino groups and the chain groups of the polylactic acid in the spinning solution to obtain an aminated polylactic acid fiber membrane.

[0008] The amino-reinforced polylactic acid-based nanofiber membrane is obtained by compounding the amino-reinforced polylactic acid-based nanofiber membrane with an electrode membrane.

[0009] As a preferred embodiment, the mass fraction of the aminated metal organic framework powder in the aminated polylactic acid fiber membrane is 1% to 10%.

[0010] As a preferred embodiment, the amino metal organic framework is NH2-ZIF-8, NH2-UiO-66 or NH2-MIL-101.

[0011] As a preferred embodiment, the molecular weight of the L-polylactic acid is (1-4)×10 5 The molecular weight of dextrorotatory polylactic acid is (0.5~2)×10 5 The mass ratio of dextrorotatory polylactic acid to l-rotatory polylactic acid is 1:99 to 99:1.

[0012] As a preferred embodiment, the parameters of the electrospinning are: output voltage of 25 kV to 50 kV, spinning temperature of 20° C. to 50° C., and spinning humidity of 20% to 40%.

[0013] As a preferred embodiment, during electrospinning, the consumption rate of the blended liquid is 0.1 mL / h to 2 mL / h, and the fiber winding rate is 500 rpm to 5000 rpm.

[0014] As a preferred embodiment, the electrode film is one or two of a copper mesh electrode, a silver nanowire electrode, and a silver mesh electrode.

[0015] As a preferred embodiment, the gap between the amino polylactic acid fiber membrane and the electrode membrane is 0.1 mm to 0.5 mm.

[0016] As a preferred embodiment, the average fiber diameter of the amino polylactic acid fiber membrane is 0.01-1.5 μm, and the obtained fiber membrane has a gram weight of 2.0-7.5 g / m 2 .

[0017] The second object of the present invention is to provide an amino-reinforced polylactic acid-based nanofiber membrane prepared by the above-mentioned preparation method.

[0018] The third object of the present invention is to provide an application of the above-mentioned amino-reinforced polylactic acid-based nanofiber membrane in air filtration.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] The present invention provides an active site for hydrogen bond formation by introducing highly active amino groups. When the amino groups meet the polylactic acid chain groups, hydrogen bonds are generated. Therefore, the present invention greatly increases the hydrogen bond density by introducing the aminated metal organic framework material, and the increase in hydrogen bond density strengthens the crystallization rate (crystallization kinetics) of polylactic acid, promotes the chain phase change, and further promotes the formation of stereocomplexation, thereby obtaining an aminated polylactic acid fiber membrane (MSC-PLA fiber membrane), which provides a triboelectric nanogenerator basis, and can stably collect charges and form an electric potential field by being compounded with an electrode membrane. The present invention forms a triboelectric nanogenerator structure by combining membranes, thereby obtaining an amino-reinforced polylactic acid-based nanofiber membrane with high electrical activity, antimicrobial activity, excellent PMs filtration effect, and low filtration resistance, and long-term storage will not affect the potential of the filter material.

[0021] The amino-reinforced polylactic acid prepared by the present invention has a PMs filtration efficiency of 99.0% to 99.99%, a surface potential maintained at 12 to 18 kV, a respiratory resistance of 90 to 180 Pa, an antiviral efficiency of 99.0% to 99.98%, and a bacterial filtration efficiency of 99.2% to 99.98%. The present invention provides a high-performance air filtration membrane with broad application prospects and a preparation method thereof, and the invention has a significant positive effect on the triboelectric properties of traditional polylactic acid filtration membranes. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The present invention is a process flow chart for preparing the amino-reinforced polylactic acid-based nanofiber membrane. DETAILED DESCRIPTION

[0023] In order to enable those skilled in the art to better understand the technical solution of the present invention and implement it, the present invention is further described below in conjunction with specific examples, but the examples are not intended to limit the present invention. The following test methods and detection methods, unless otherwise specified, are conventional methods; the reagents and raw materials, unless otherwise specified, are commercially available.

[0024] The existing polylactic acid chain mentioned in the background technology of the present invention has a small number of active groups and a low degree of polarization, which leads to the technical problem that the tensile strength and triboelectric effect of polylactic acid are not good. Based on the above technical problems, the present invention provides an amino-reinforced polylactic acid-based nanofiber membrane and a preparation method and application thereof. The present invention strengthens the stereocomplexation of polylactic acid through an amino metal organic framework material, enhances the electrical activity and gas separation ability of the nanofiber membrane, and enables the fiber membrane to have the characteristics of harmful gas separation, high efficiency, low resistance, and antibacterial.

[0025] The technical solution of the present invention is analyzed and explained in detail below.

[0026] The present invention first provides a method for preparing an amino-reinforced polylactic acid-based nanofiber membrane, comprising the following steps:

[0027] The left-handed polylactic acid and the right-handed polylactic acid are used as raw materials, respectively dissolved in a solvent to obtain a first spinning solution and a second spinning solution, and then mixed to obtain a spinning solution.

[0028] The solvent is at least one of dimethyl carbonate (DMC), N-dimethylformamide (DMF), dichloromethane and chloroform.

[0029] The aminated metal organic framework powder is added to the spinning solution to obtain a blended solution, and the blended solution is electrospun to form a hydrogen bond between the amino group and the chain group of the polylactic acid in the spinning solution to obtain an aminated polylactic acid fiber membrane, the average fiber diameter is 0.01 to 1.5 μm, and the obtained fiber membrane has a gram weight of 2.0 to 7.5 g / m 2 .

[0030] The amino-reinforced polylactic acid-based nanofiber membrane is obtained by compounding the amino-reinforced polylactic acid-based nanofiber membrane with an electrode membrane.

[0031] In the above technical scheme, an amino-modified polylactic acid fiber membrane (MSC-PLA fiber membrane) is obtained by introducing highly active amino groups to increase the hydrogen bond density and promote the formation of stereocomplexation. The MSC-PLA fiber membrane provides the basis of a triboelectric nanogenerator, and can stably collect charges and form an electric potential field by being compounded with an electrode membrane. The triboelectric nanogenerator structure is formed by combining the membranes, thereby obtaining an amino-reinforced polylactic acid-based nanofiber membrane with high electrical activity, antimicrobial activity, excellent PMs filtration effect and low filtration resistance, and long-term storage will not affect the potential of the filter material.

[0032] As a preferred embodiment, the mass fraction of the aminated metal organic framework powder in the aminated polylactic acid fiber membrane is 1% to 10%. The mass fraction of the aminated metal organic framework powder is limited to control the strength of the stereocomplex. Too little left-handed polylactic acid or right-handed polylactic acid cannot achieve the ideal stereocomplex effect, the stereocomplex strength is low, and the spinning result will also be adversely affected.

[0033] As a preferred embodiment, the amino metal organic framework is NH2-ZIF-8, NH2-UiO-66 or NH2-MIL-101.

[0034] It should be noted that the above-mentioned preparation methods of the aminated metal organic framework are all obtained by using an aminated precursor solution through a sol-gel method, a coprecipitation method or a microwave synthesis method. After the reaction is completed, it is washed with deionized water, methanol or DMF and dried for 12h to 72h.

[0035] The precursor solution of the metal organic framework NH2-UiO-66 is a mixed solution of chromium chloride, diaminoterephthalic acid and acetic acid.

[0036] The precursor solution of the metal organic framework NH2-ZIF-8 is a mixed solution of aluminum acetate, dimethylimidazole, 2-aminobenzimidazole, deionized water and CTAB.

[0037] The precursor solution of the metal organic framework MIL-101 is a mixed solution of ultrapure water, Fe(NO3)3-9H2O powder, DMF, and 2-aminoterephthalic acid.

[0038] As a preferred embodiment, the molecular weight of the L-polylactic acid is (1-4)×10 5 The molecular weight of dextrorotatory polylactic acid is (0.5~2)×10 5 The mass ratio of D-PLA to L-PLA is 1:99 to 10:90. The molecular weight of L-PLA and D-PLA is greater than 100,000, and the viscosity of the spinning solution is sufficient to support the spinning process. The molecular weight range given here is the molecular weight range with the best electrospinning effect. If it is larger or smaller, the effect is not good.

[0039] As a preferred embodiment, the electrospinning parameters are: output voltage of 25kV to 50kV, spinning temperature of 20℃ to 50℃, spinning humidity of 20% to 40%; during electrospinning, the consumption rate of the blended liquid is 0.1mL / h to 2mL / h, and the fiber winding rate is 500rpm to 5000rpm. For the above-mentioned fiber winding rate, the winding speed mainly affects the fiber thickness and is a relatively important indicator. The fiber is thick at a low speed and thin at a high speed, but the roller cannot withstand too high a speed, so the present invention selects the above-mentioned electrospinning parameter group in the experimental exploration.

[0040] As a preferred embodiment, the electrode film is one or two of a copper mesh electrode, a silver nanowire electrode, and a silver mesh electrode.

[0041] In order to ensure the best triboelectric effect of the fiber membrane, the gap between the amino polylactic acid fiber membrane and the electrode membrane is 0.1mm to 0.5mm. A small gap must be ensured between the electrode membrane and the polylactic acid membrane to achieve the triboelectric effect. If they are completely attached together, there will be no relative movement and no friction effect. If the distance is too far, the breathing vibration cannot make the membranes contact each other, and the triboelectric effect cannot be achieved.

[0042] The technical effects of the present invention are described in detail below through specific embodiments and comparative examples.

[0043] Example 1

[0044] A method for preparing an amino-reinforced polylactic acid-based nanofiber membrane comprises the following steps:

[0045] S1. Preparation of spinning solution (MSC-PLA spinning solution): 0.99 g of 1×10 5 of poly(L-lactic acid) (PLLA) and 0.01 g of molecular weight of 0.5×10 5 The dextrorotatory polylactic acid (PDLA) was dissolved in 10 mL of a DMF+DMC mixed solution with a volume ratio of 3:7. The PDLA and PLLA solutions were mixed and stirred for 0.5 h until they were evenly mixed to obtain a spinning solution with a polylactic acid mass concentration of 0.1 g / mL.

[0046] S2. Preparation of aminated metal organic framework (aminated MOF) powder: ultrasonically treat a mixed solution of chromium chloride, diaminoterephthalic acid and acetic acid, i.e., the aminated precursor solution of UIO-66, for 3 min, and process it by solution-gel method (PTFE reactor insulation time 72 h, washing liquid is deionized water), and dry it for 12 h to obtain aminated UIO-66 powder.

[0047] S3. Preparation of amino polylactic acid fiber membrane (MSC-PLA fiber membrane): The amino UIO-66 powder was added to the spinning solution at a mass ratio of 1wt%, and the average fiber diameter was 1.5μm and the weight was 7.5g / m by single-needle electrospinning technology (output voltage 25kV, solution consumption rate 0.1mL / h, roller speed 500rmp, spinning temperature 20°C, spinning humidity 40%). 2 MSC-PLA fiber membrane.

[0048] S4. Preparation of amino-reinforced polylactic acid nanofiber membrane: The MSC-PLA fiber membrane obtained in S3 is combined with an electrode membrane according to a sandwich structure of "copper mesh electrode membrane-MSC-PLA fiber membrane-silver nanowire electrode membrane" to obtain an amino-reinforced polylactic acid-based nanofiber membrane.

[0049] Example 2

[0050] A method for preparing an amino-reinforced polylactic acid-based nanofiber membrane comprises the following steps:

[0051] S1. Preparation of MSC-PLA spinning solution: 0.01 g of MSC-PLA with a molecular weight of 4×10 5 0.99 g of PLLA and a molecular weight of 3 × 10 5 PDLA was dissolved in 33 mL of a DMF+DMC mixed solution with a volume ratio of 3:7. The PDLA and PLLA solutions were mixed and stirred for 2 h until they were uniformly mixed to obtain a spinning solution with a polylactic acid mass concentration of 0.03 g / mL.

[0052] S2. Preparation of aminated MOF powder: The mixed solution of chromium chloride, diaminoterephthalic acid and acetic acid, i.e., the aminated precursor solution of UIO-66, was sonicated for 20 min, processed by coprecipitation method (PTFE reactor insulation time 72 h, washing liquid is methanol), and dried for 72 h to obtain aminated UIO-66 powder.

[0053] S3. Preparation of MSC-PLA fiber membrane: The amino UIO-66 powder was added into the spinning solution at a mass ratio of 4 wt%, and the average fiber diameter was 0.1 μm and the weight was 2 g / m by single-needle electrospinning technology (output voltage 50 kV, solution consumption rate 2 mL / h, roller speed 5000 rpm, spinning temperature 20 ° C, spinning humidity 40%). 2 MSC-PLA fiber membrane.

[0054] S4. Preparation of amino-reinforced polylactic acid-based nanofiber membrane: The MSC-PLA fiber membrane obtained in S3 is combined with an electrode membrane according to the structure of "silver mesh electrode membrane-MSC-PLA fiber filter membrane" to obtain an amino-reinforced polylactic acid-based nanofiber membrane.

[0055] Example 3

[0056] A method for preparing an amino-reinforced polylactic acid-based nanofiber membrane comprises the following steps:

[0057] S1. Preparation of MSC-PLA spinning solution: 2 g of MSC-PLA with a molecular weight of 4×10 5 The molecular weight of PLLA is 3×10 5 PDLA was dissolved in 10 mL of a DMF+DMC mixed solution with a volume ratio of 3:7. The PDLA and PLLA solutions were mixed and stirred for 1 h until they were evenly mixed to obtain a spinning solution with a polylactic acid mass concentration of 0.4 g / mL.

[0058] S2. Preparation of aminated MOF powder: The aminated MIL-101 precursor solution, i.e., a mixed solution of ultrapure water, Fe(NO3)3-9H2O powder, DMF and 2-aminoterephthalic acid, was vigorously stirred and ultrasonicated for 15 min, processed by microwave-assisted synthesis (microwave-assisted synthesis power 60 W, temperature 140°C, insulation for 10 min, washing liquid is methanol), dried for 12 h, and the aminated MIL-101 powder was obtained.

[0059] S3. Preparation of MSC-PLA fiber membrane: The amino-modified MIL-101 powder was added to the spinning solution at a mass ratio of 10 wt%, and the average fiber diameter was 0.9 μm and the weight was 6 g / m by double-needle electrospinning technology (output voltage 30 kV, solution consumption rate 1 mL / h, roller speed 3000 rpm, spinning temperature 30 ° C, spinning humidity 60%).2 MSC-PLA fiber membrane.

[0060] S4. Preparation of amino-reinforced polylactic acid-based nanofiber membrane: The MSC-PLA fiber membrane obtained in S3 is combined with an electrode membrane according to the structure of "copper mesh electrode membrane-MSC-PLA fiber filter membrane-silver mesh electrode membrane" to obtain an amino-reinforced polylactic acid-based nanofiber membrane.

[0061] Example 4

[0062] A method for preparing an amino-reinforced polylactic acid-based nanofiber membrane comprises the following steps:

[0063] S1. Preparation of MSC-PLA spinning solution: 1.5 g of MSC-PLA with a molecular weight of 2×10 5 The molecular weight of PLLA is 1.5×10 5 The PDLA were dissolved in 10 mL of a DMF+DMC mixed solution with a volume ratio of 3:7, and the PDLA and PLLA solutions were mixed and stirred for 0.5 h until they were uniformly mixed to obtain a spinning solution with a polylactic acid mass concentration of 0.25 g / mL.

[0064] S2. Preparation of aminated MOF powder: The mixed solution of aluminum acetate, dimethylimidazole, 2-aminobenzimidazole, deionized water and CTAB, i.e., the precursor solution of aminated ZIF-8, was sonicated for 20 min, processed by microwave-assisted synthesis (microwave-assisted synthesis power 60 W, temperature 140° C., insulation for 10 min, washing liquid is methanol), and dried for 72 h to obtain aminated ZIF-8 powder.

[0065] S3. Preparation of MSC-PLA fiber filtration membrane: The amino ZIF-8 powder was added to the spinning solution at a mass ratio of 6 wt%, and the average fiber diameter was 1.2 μm and the weight was 5 g / m by double-needle electrospinning technology (output voltage 40 kV, solution consumption rate 1.5 mL / h, roller speed 1500 rpm, spinning temperature 40°C, spinning humidity 50%). 2 MSC-PLA fiber membrane.

[0066] S4. Preparation of amino-reinforced polylactic acid-based nanofiber membrane: The MSC-PLA fiber membrane obtained in S3 is combined with an electrode membrane according to the structure of "copper mesh electrode membrane-MSC-PLA fiber filter membrane-copper mesh electrode membrane" to obtain an amino-reinforced polylactic acid-based nanofiber membrane.

[0067] In order to further illustrate the technical effect of the present invention, the present invention also sets a comparative example, which is as follows:

[0068] Comparative Example 1

[0069] Compared with Example 1, the difference is that instead of using amino-reinforced polylactic acid-based nanofiber membrane as the middle layer, polylactic acid nonwoven fabric (weight 18 g / m 2 ), and then combine it with the silver nanowire electrode membrane in the structure of "silver nanowire electrode membrane-polylactic acid non-woven fabric-silver nanowire electrode membrane" to obtain a filtration membrane.

[0070] A method for preparing a polylactic acid nonwoven fabric-based nanofiber membrane comprises the following steps:

[0071] The weight is 18g / m 2 The polylactic acid nonwoven fabric is combined with the electrode membrane according to the sandwich structure of "silver nanowire electrode membrane-polylactic acid nonwoven fabric-silver nanowire electrode membrane" to obtain the polylactic acid nonwoven fabric-based nanofiber membrane.

[0072] Comparative Example 2

[0073] Compared with Example 2, the difference is that instead of using an amino-containing organic metal skeleton as filler, ordinary UIO-66 powder is used as filler, and a non-amino-reinforced stereocomposite fiber filter membrane is prepared by electrospinning, and the copper mesh and the SC-PLA fiber membrane are combined into a "copper mesh electrode membrane-non-amino-reinforced stereocomposite fiber filter membrane-copper mesh electrode membrane" to obtain a filter membrane.

[0074] A method for preparing a polylactic acid-based nanofiber membrane comprises the following steps:

[0075] S1. Preparation of MSC-PLA spinning solution: 0.01 g of MSC-PLA with a molecular weight of 4×10 5 0.99 g of PLLA and a molecular weight of 3 × 10 5 PDLA was dissolved in 33 mL of a DMF+DMC mixed solution with a volume ratio of 3:7. The PDLA and PLLA solutions were mixed and stirred for 2 h until they were uniformly mixed to obtain a spinning solution with a polylactic acid mass concentration of 0.03 g / mL.

[0076] S3. Preparation of MSC-PLA fiber membrane: Ordinary UIO-66 powder was added into the spinning solution at a mass ratio of 4 wt%, and single-needle electrospinning technology (output voltage 50 kV, solution consumption rate 2 mL / h, roller speed 5000 rpm, spinning temperature 20 ° C, spinning humidity 40%) was used to prepare the average fiber diameter of 0.1 μm and gram weight of 2 g / m 2 Non-amino reinforced polylactic acid based fiber membrane (SC-PLA fiber membrane).

[0077] S4. Preparation of amino-reinforced polylactic acid-based nanofiber membrane: The SC-PLA fiber membrane obtained in S3 is combined with an electrode membrane according to the structure of "copper mesh electrode membrane-SC-PLA fiber membrane-copper mesh electrode membrane" to obtain a polylactic acid-based nanofiber membrane.

[0078] Comparative Example 3

[0079] Compared with Example 3, the difference is that the filter membrane of N95 mask (brand 3M 9132) is used instead of MSC-PLA fiber membrane for performance testing, and the filter membrane is obtained by the combination of "copper mesh electrode membrane-N95 filter membrane-copper mesh electrode membrane".

[0080] The properties of the amino-reinforced polylactic acid-based nanofiber membranes prepared in Examples 1 to 4 of the present invention and Comparative Examples 1 to 3 were characterized and tested, and the results are as follows.

[0081] Structural characterization and performance testing:

[0082] Scanning electron microscopy: The microstructure of the PLA fiber membrane and the silver nanofiber membrane was observed by field emission scanning electron microscopy (model JSM-7900F, JEOL).

[0083] Dielectric constant test: The dielectric constant was tested using a dielectric constant tester (model Wayne Kerr 6500B, Wayne Kerr, UK).

[0084] Respiratory resistance test: A micromanometer (AIRPROAP800, TSI, USA), anthropomorphic respirator and simulated human head were used to measure respiratory resistance. The gas flow rate was set to 85L / min, and the filter membrane was encapsulated on the simulated human head. The air pressure of the cavity formed by the filter membrane and the human head and the atmospheric pressure were measured and the difference was made. The experiment was repeated three times and the average value was taken to calculate the respiratory resistance of the filter membrane.

[0085] Surface potential test: A non-contact electrostatic meter (VM54XQS, Quatek, USA) was used to test the surface potential of the nanofiber membrane. The test height was 2 cm, the temperature and humidity were constant at 25°C and 45%, and 20 data points were randomly collected for each sample and the average value was taken.

[0086] Filtration performance test: NaCl was selected as the test aerosol (Model 8026 aerosol generator, TSI, USA). The size of the PM particles generated was between 10nm and 10μm. Four flow rates of 10L / min, 32L / min, 65L / min, and 85L / min were used to simulate the wearer's different breathing states (resting breathing, normal breathing, rapid breathing, and rapid breathing) to test the filtration performance. The fiber membrane was cut into discs with a diameter of 120mm, and then the membrane was placed in the assembled filter device and fixed. The filtration efficiency (3910 Nanoparticle Sizer (SMPS), 3310 Optical Particle Sizer (OPS), TSI, USA) and pressure drop (ModelAP800 micromanometer, TSI, USA) were measured in the homemade PM filtration test equipment.

[0087] CO2 adsorption test: The gas adsorption isotherm of carbon dioxide (99.999%) was analyzed using a 3Flex 3500 surface characterization analyzer (Micromeritics Instrument Corporation, USA). The low temperature was controlled by a Dewar flask (4 L) filled with dry ice and acetone. The water bath temperature was controlled by a water bath (Changzhou First Textile Equipment Co., Ltd.). Before collecting the adsorption isotherm, the material was pre-degassed at room temperature for 16 hours.

[0088] CO adsorption test: The adsorption isotherm of CO (99.996%) was measured using an automatic volumetric adsorption instrument BELSORP-max (MicrotracBel, Japan) connected to a cryostat system. The sample was placed on a copper plate and evacuated for 12 hours under a dynamic vacuum at room temperature to remove the guest molecules. The weight of the evacuated sample was measured under an inert gas and placed in a cryostat system before the experiment under a high vacuum (pressure less than 10 -3 The sample was vacuumed for 2 h at 400 Pa and the temperature was controlled to control the CO2 gas to enter the sample. The degree of adsorption was determined by the decrease in the pressure of the introduced gas at equilibrium.

[0089] Table 1 Test results of respiratory resistance, surface potential and filtration performance of amino-reinforced polylactic acid-based nanofiber membrane of the present invention

[0090]

[0091]

[0092] Table 2 Antiviral test results of amino-reinforced polylactic acid-based nanofiber membranes

[0093]

[0094] Table 3 Microbial inactivation test results of amino-reinforced polylactic acid-based nanofiber membranes

[0095]

[0096] Table 4 Gas separation test results of amino-reinforced polylactic acid-based nanofiber membrane (298K)

[0097]

[0098] The surface potential, filtration efficiency, respiratory resistance, tensile strength, antiviral, antibacterial and filtration efficiency of the amino-reinforced polylactic acid-based nanofiber membrane prepared by the present invention were tested, and the results are shown in Tables 1 to 4. The amino-reinforced polylactic acid-based nanofiber membrane of the present invention has a filtration efficiency of 99.0% to 99.99% for PMs, a surface potential maintained at 12kV to 18kV, a respiratory resistance of 90Pa to 180Pa, an antiviral efficiency of 99.0% to 99.98%, and a bacterial filtration efficiency of 99.2% to 99.98%.

[0099] The experiment adopted 4 groups of embodiments and 3 groups of comparative examples. The test results showed that increasing the content of amino MOF can effectively increase the triboelectricity of the filter membrane, the ability to store charge and improve the filter membrane's ability to screen CO2, and successfully separate CO from CO2. However, the maximum addition amount is 10wt%, which can maintain the surface potential at about 18kV, and the amount of electricity does not change much within 30 days. Changing the content ratio of PDLA and PLLA in the range of 1:99 to 99:1 has little effect on the results; the silver nanowire electrode membrane has the best antibacterial performance, but considering the cost, the combination of the copper mesh electrode membrane and the silver nanowire electrode membrane has the highest cost performance. The filter membrane prepared according to the present invention can maintain the bacterial filtration efficiency at 99.0% to 99.98%, and the antiviral efficiency can reach 99.0% to 99.98%. Therefore, the experimental conditions changed in the 4 groups of embodiments will not have a great impact on the experimental results, that is, the experiment is feasible.

[0100] In the three groups of comparative examples, the purchased polylactic acid non-woven fabric was used to replace the amino-reinforced polylactic acid stereocomposite self-powered fiber filter membrane, the non-amino-reinforced stereocomposite polylactic acid fiber filter membrane was used to replace the amino-reinforced polylactic acid stereocomposite self-powered fiber filter membrane, and the electret filter membrane of the N95 mask was used to replace the high-porosity SC-PLA fiber membrane. Experimental comparisons were made. The results showed that the purchased polylactic acid non-woven fabric could not achieve the same triboelectric effect as the high-porosity SC-PLA fiber membrane of electrospinning, which would greatly affect its effect of maintaining surface potential for a long time, filtering and inactivating microorganisms, and adsorbing and capturing PMs, and the breathing resistance was significantly increased, and it could not be done. The present invention proposes the requirements of low filtration resistance, microbial inactivation and long-term effect; if MOF is not used as a filler, the requirement of a large number of hydrogen bonds promoting the degree of stereocomplexation cannot be met, and the electrical activity of the fiber filter membrane and the PMs filtration efficiency will be greatly reduced; the method of replacing the high-porosity SC-PLA fiber membrane with the electret filter membrane of the N95 mask will greatly increase the respiratory resistance of the filter membrane. If it is put into production and use, the human body may have obvious discomfort, and its filtration and inactivation effects on viruses are very poor. Except for the sample in which only the electrode is replaced and the amino-modified MIL-101 is used, the comparison example has a very poor gas separation effect, which cannot meet the requirements of low filtration resistance, microbial inactivation and effective gas separation proposed by the present invention.

[0101] According to the comprehensive observation of the embodiments and comparative examples, the amino-enhanced polylactic acid stereocomplexed self-powered fiber filter membrane has significantly improved the filtration efficiency of PMs and bacteria, and the inactivation ability of viruses compared with the traditional polylactic acid filter membrane, and significantly improved the surface potential of the filter membrane and significantly reduced the respiratory resistance. Therefore, the experimental method proposed in the present invention is feasible and the product produced meets expectations, and the materials used are reasonable, so the present invention provides a high-performance air filter membrane with broad application prospects.

[0102] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A method for preparing an amino-reinforced polylactic acid-based nanofiber membrane, characterized in that: The following steps are involved: Using left-handed polylactic acid and right-handed polylactic acid as raw materials, dissolving them in solvents respectively to obtain a first spinning solution and a second spinning solution, and mixing them to obtain a spinning solution; Adding the aminated metal organic framework powder to the spinning solution to obtain a blended solution, and electrospinning the blended solution to form hydrogen bonds between the amino groups and the chain groups of the polylactic acid in the spinning solution to obtain an aminated polylactic acid fiber membrane; The amino-reinforced polylactic acid-based nanofiber membrane is obtained by compounding the amino-reinforced polylactic acid-based nanofiber membrane with an electrode membrane.

2. The preparation method according to claim 1, characterized in that: The mass fraction of the aminated metal organic framework powder in the aminated polylactic acid fiber membrane is 1% to 10%.

3. The preparation method according to claim 1, characterized in that: The aminated metal organic framework is NH2-ZIF-8, NH2-UiO-66 or NH2-MIL-101.

4. The preparation method according to claim 1, characterized in that: The electrospinning parameters are: output voltage of 25kV to 50kV, spinning temperature of 20°C to 50°C, spinning humidity of 20% to 40%; the consumption rate of the blended liquid is 0.1mL / h to 2mL / h, and the fiber winding rate is 500rpm to 5000rpm.

5. The preparation method according to claim 1, characterized in that: The gap between the amino polylactic acid fiber membrane and the electrode membrane is 0.1 mm to 0.5 mm.

6. The preparation method according to claim 1, characterized in that: The electrode film is one or two of a copper mesh electrode, a silver nanowire electrode, and a silver mesh electrode.

7. The preparation method according to claim 1, characterized in that: The molecular weight of the L-polylactic acid is (1-4)×10 5 The molecular weight of dextrorotatory polylactic acid is (0.5~2)×10 5 The mass ratio of dextrorotatory polylactic acid to l-rotatory polylactic acid is 1:99 to 99:

1.

8. The preparation method according to claim 1, characterized in that: The average fiber diameter of the amino polylactic acid fiber membrane is 0.01-1.5 μm, and the obtained fiber membrane has a gram weight of 2.0-7.5 g / m 2 .

9. An amino-reinforced polylactic acid-based nanofiber membrane prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the amino-reinforced polylactic acid-based nanofiber membrane according to claim 9 in air filtration.

Citation Information

Patent Citations

  • A high-adsorption porous composite film used for adsorbing PM2.5

    CN106988017A

  • Polylactic acid racemic blend doped NH2-MIL-88 electrode material as well as preparation method and application thereof

    CN114914095A

  • Friction self-powered stereocomplex polylactic acid nanofiber membrane for ultra-long-acting filtration and preparation method of friction self-powered stereocomplex polylactic acid nanofiber membrane

    CN115970400A

  • High-porosity self-powered stereocomplex polylactic acid fiber filter membrane and preparation method thereof

    CN116712874A

  • In-situ MOF stereocomplex polylactic acid micro / nano fiber self-powered filter membrane and preparation method thereof

    CN116726729A